Penerapan Model AISAS Pada Promosi Digital Penerimaan Mahasiswa Baru (PMB) Institut Bisnis dan Informatika Kosgoro 1957 - Pranawukir, Iswahyu; Hamboer, Maria Jashinta Elisabet (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Sekolah Tinggi Ilmu Sosial dan Ilmu Politik (STISIPOL) Candradimuka Palembang, 2022)
The focus of this study is to analyze the IBI-K57 digital marketing communications in influencing the AISAS behavior among new students. The sub focus of this research is to find out and measure the level of student interest in AISAS (attention, interest, search, action and share) when making decisions to enter. This research utilise the campus digital marketing communications, namely: trustworthiness and expertise, combined with the AISAS method. Furthermore, the quantitative methodology of the positivistic paradigm of the sociopsychological communication tradition, which accompanied by simple linear regression analysis, is also applied. Sampling of the survey was carried out using a random technique. Each program studies is given 20 samples of questionnaire with a Likert scale. The total number of questioners is 120. The ANOVA value of 0.000 (<0.05) in this study shows there are changes in student attitudes and behavior in selecting the program study. Digital marketing communications has influenced students’ AISAS (behavioral attitudes), which is 36.4%. The remaining value (60.4%) is coming from other aspects outside the digital marketing communications. This research shows that there is a significant and positive influences of digital marketing communications applied by IBI-K57 on the attitudes and behavior (AISAS) of students when determining final decision to study in this institution. Digital marketing communications has contributed to a twofold attitude change among students in deciding.